Konstruksi Maskulinitas dan Feminitas dalam Tafsir Marrah Labid - Adam Farhan Maliki; Siti Masykuroh; Ahmad Muttaqin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Gender studies in Qur'anic exegesis continue to develop, yet research on classical tafsir remains largely limited to identifying patriarchal biases or contemporary reinterpretations, while studies that position tafsir as a historical product shaped by the social, cultural, and intellectual contexts of the exegete remain relatively scarce. This article analyzes the construction of masculinity and femininity in Tafsir Marrah Labid by Shaykh Nawawi al-Bantani and explains the underlying context that shaped these constructions. The research employs a qualitative method based on library research with a historical-critical approach and content analysis. Primary data are drawn from Tafsir Marrah Labid, while secondary data are obtained from journals, books, and relevant previous studies. The analysis focuses on the exegesis of gender-related verses, namely QS. al-Baqarah: 187, 228, 282, QS. ar-Rum: 21, QS. an-Nisa': 34, QS. al-Ahzab: 33, and QS. at-Tahrim: 10–12. The findings show that masculinity is constructed through leadership, financial provision, protection, moral authority, and socio-legal spheres, whereas femininity is constructed through piety, honor, biological trust, obedience, and spiritual steadfastness. Shaykh Nawawi's interpretation does not reflect a merely dominant relationship but demonstrates principles of reciprocity, public welfare (maslahah), and ethical responsibility. The gender construction in this tafsir emerges from the interaction between the Qur'anic text, classical exegetical tradition, the school of jurisprudence (madhhab) adhered to, and the socio-intellectual context of the 19th century